Pengaruh Pelatihan Kerja Dan Kompensasi Finansial Terhadap Kinerja Pegawai Dengan Pengembangan Karir Sebagai Variabel Intervening Pada SMAN 01 Basa Ampek Balai Tapan - Olivia Permata Saria; Yulasmi; Selvi Yona Sari (CV. ITTC INDONESIA, 2025)
The purpose of this study was to determine how much influence Job Training and Financial Compensation have on Employee Performance Through Career Development at SMAN 01 Basa Ampek Balai Tapan, The sample used was a saturated sample, because the entire population was sampled, namely 81 respondents. Data collection techniques through questionnaires that have been tested for validity and reliability, Partial Least Square (PLS) was used to test the hypothesis in this study using SmartPLS 3.0. The results of this study indicate that Job Training has a significant effect on Career Development. There is Financial Compensation that has a significant effect on Career Development. There is Job Training that has no effect and is not significant on employee performance. There is Financial Compensation that has a significant effect on Employee Performance. There is Career Development has no effect and is not significant on Employee Performance. There is Job Training does not mediate Employee Performance through Career Development. There is Financial Compensation does not mediate Employee Performance through Career Development.